KARAKTERISASI KUAT TEKAN BETON AGREGAT LOKAL DENGAN VARIASI SUPERPLASTICIZER PADA UMUR AWAL: KARAKTERISASI KUAT TEKAN BETON AGREGAT LOKAL DENGAN VARIASI SUPERPLASTICIZER PADA UMUR AWAL - Kukuh Kurniawan Dwi Sungkono; Wijayanti, Paska; Prasetyo, Erwin aji; Kurniawan, Rizal; Khoirudin, Wahyu; Izzudin, Daffa Zaidan Alam (Jurnal Teknik Sipil dan Arsitektur, 2025)
This study aims to characterize the effect of superplasticizer addition on local aggregate concrete workability and early-age compressive strength. The methodology involved the use of Portland Composite Cement, local fine and coarse aggregates, and Fosroc Auracast SP310 superplasticizer at dosages of 1%, 1.6%, and 2%. Four concrete mix designs were prepared: normal concrete (BN) and concrete with superplasticizer additions (BN-1%, BN-1.6%, BN-2%). Slump and compressive strength tests were conducted according to Indonesian standards to assess workability and strength at 7 and 14 days. Results indicate that superplasticizer addition significantly improves concrete workability with slump values ranging from 560 to 630 mm compared to 115 mm for the control. Compressive strength also increased markedly, with BN-2% showing the highest strength at 38.56 MPa at 7 days and 51.94 MPa at 14 days. The study concludes that superplasticizer effectively enhances both workability and compressive strength without increasing water demand, resulting in denser and stronger concrete at early curing ages.